Tanggapan Konsumen tentang Manfaat Virgin Coconut Oil (VCO) untuk Kesehatan (Studi Kasus) - Irwan Hanafi (Eduscience Development Journal, 2022)
In its utilization, VCO can be consumed directly or used for cooking with many benefits for health, preventing and curing various diseases. The research entitled "Consumer Responses About the Benefits of Virgin Coconut Oil (VCO) for Health" was carried out from September to October 2020 in Solok City. by distributing questionnaires to VCO consumers. Based on the results of the study, respondents were very satisfied with the benefits obtained by consuming VCO because it was proven that VCO could cure the diseases they suffered. After analyzing the data, it was obtained that rxy = 0.75, where the X variable and Y variable had a unidirectional relationship in the strong category. That is, the longer a person consumes VCO, the better his health will be.